Climate extremes, average conditions and temperature variability as drivers of dengue epidemics in a temperate city of Argentina - María S. López; Miguel A. Lovino; Andrea A. Gómez; Santiago T. Rodríguez; Ainelen L. Radosevich; Gabriela V. Müller; Elizabet L. Estallo (The Journal of Climate Change and Health)
Introduction: Climate change represents one of the greatest health threats of our time, and is associated with the expansion of mosquito-borne viruses globally. Argentina has experienced long-term changes in precipitation and temperature, enhancing the climatic suitability for dengue transmission. This study assesses climate extremes, average climate conditions, and temperature variability and their relationships with dengue epidemics in a city with temperate climate in central Argentina. Methods: A set of descriptive indices for temperature and precipitation extremes was analyzed to detect long-term changes and variability in climate extremes from 1940 to 2022, as well as temperature variability during major dengue epidemics in 2020 and 2023. To evaluate the influence of the climate on epidemics, time series of cases and climatic variables were analyzed, generalized linear models were applied, and a mathematical model was used to estimate the number of days required for the transmission of the dengue virus. Results: Some climate extreme indices may influence the increase in dengue cases in the city of Reconquista. Average temperature and precipitation were noted to shape the seasonality and temporality (onset, development, and end) of the dengue epidemics. Temperature variability has impacted the extrinsic incubation period, thereby shaping the magnitude and duration of the dengue epidemics. Conclusion: The analysis of long-term climate data reveals that rising temperatures and some associated extremes are significant factors driving this trend, with implications for public health preparedness and response. We emphasize the necessity for enhancing monitoring systems, encompassing epidemiological, climatic, and vector variables, to mitigate the impacts of future epidemics.